2017
DOI: 10.1002/nau.23296
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as potential biomarkers to predict the risk of urinary retention following intradetrusor onabotulinumtoxin‐A injection

Abstract: Aims: MicroRNAs (miRs) control post-transcriptional gene expression, and this is relevant in understanding better chronic diseases and treatment outcomes. The role of miRs in the pathology and treatment outcomes of overactive bladder (OAB) is unknown. In this study, we assessed the differential expression of miRs in OAB patients responding with either normal or elevated post-void residual volumes (PVRs) ≥200 mL following intradetrusor injection of onabotulinumtoxin-A (onaBoNT-A). Methods: Female OAB patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Kashyap et al found that miR‐132 and miR‐221 were dysregulated in rat OAB models, and these miRNAs were effective in bladder hypertrophy and dysfunction. Chermansky et al also associated dysregulation of miR‐221 and miR‐125b with patients with OAB . Cordes et al reported that miR‐143 and miR‐145 regulate smooth muscle tone, and Imamura et al also stated that miR‐1 may be a new therapeutic target in OAB with the role of reducing the smooth muscle contraction of the bladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kashyap et al found that miR‐132 and miR‐221 were dysregulated in rat OAB models, and these miRNAs were effective in bladder hypertrophy and dysfunction. Chermansky et al also associated dysregulation of miR‐221 and miR‐125b with patients with OAB . Cordes et al reported that miR‐143 and miR‐145 regulate smooth muscle tone, and Imamura et al also stated that miR‐1 may be a new therapeutic target in OAB with the role of reducing the smooth muscle contraction of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Chermansky et al 24 also associated dysregulation of miR-221 and miR-125b with patients with OAB. 24 Cordes et al 25 reported that miR-143 and miR-145 regulate smooth muscle tone, and Imamura et al 26 also stated that miR-1 may be a new therapeutic target in OAB with the role of reducing the smooth muscle contraction of the bladder. The current study also supported the view that dysregulation in expression levels of miRNAs was effective in regulating smooth muscle tone in the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Additionally, nonstandard testing, such as urethral function RNA testing, or nonurologic factors may also be useful to improve model accuracy. [41][42][43] Additionally, the performance of these models was not compared to clinical experts. Although prediction models are consistently superior to clinical judgment, this remains to be directly shown for these models, and this comparison is recommended in future studies.…”
Section: T a B L E 2 Coefficients For The Prediction Modelsmentioning
confidence: 99%
“…MiRs are non-coding RNAs, approximately 19-23 nucleotides (nt) in length. They participate in epigenetic post-transcriptional control of protein-coding gene expression primarily by reversible translational repression or mRNA destabilization/ degradation and thereby inhibit protein synthesis (6).…”
Section: Original Articlementioning
confidence: 99%
“…Recently, Chermansky et al reported that the elevated expression of miR-221 and miR-125b in detrusor overactivity in the bladder tissue of patients may predict their high risk for undergoing urinary retention following intradetrusor injection of onabotulinumtoxin-A (6). In addition, the combination of upregulated miR-98-5p and downregulated miR-139-5p in the plasm of patients' overactive bladder (OAB) was found to be a useful biomarker for OAB.…”
Section: Original Articlementioning
confidence: 99%